A Simple 3, 4‐Ethylenedioxythiophene Based Hole‐Transporting Material for Perovskite Solar Cells1. (13th March 2014) - Li, Hairong; Fu, Kunwu; Hagfeldt, Anders; Grätzel, Michael; Mhaisalkar, Subodh G.; Grimsdale, Andrew C.
Abstract We report a novel electron‐rich molecule based on 3, 4‐ethylenedioxythiophene (H101). When used as the hole‐transporting layer in a perovskite‐based solar cell, the power‐conversion efficiency reached 13.8 % under AM 1.5G solar simulation. This result is comparable with that obtained using the well‐known hole transporting material 2, 2′, 7, 7′‐tetrakis(N, N‐di‐p‐methoxyphenylamine)‐9, 9′‐spirobifluorene (spiro‐OMeTAD). This is the first heterocycle‐containing material achieving >10 % efficiency in such devices, and has great potential to replace the expensive spiro‐OMeTAD given its much simpler and cheaper synthesis.